New explicit optical solitons of fractional nonlinear evolution equation via three different methods - Luu Vu Cam Hoan; Owyed, S.; İnç, Mustafa; Ouahid, L.; Abdou, M. A.; Chu, Y-M (Elsevier, 2020)
We determine optical solutions of the fractional-order Heisenberg models of ferromagnetic spin chains. We use three different techniques known as the method of new sub-equation, extended Kudryashov expansion and auxiliary equation. We express new solutions in terms of hyperbolic, rational, trigonometric functions. Computational results indicate the efficiency and potential of the methods.
Keywords: Ferromagnetic spin chains; Fractional Heisenberg models; Optical solutions; New sub-equation method; Extended Kudryashov expansion; Auxiliary equation method